3t-3t=-9+9t

Simple and best practice solution for 3t-3t=-9+9t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-3t=-9+9t equation:


Simplifying
3t + -3t = -9 + 9t

Combine like terms: 3t + -3t = 0
0 = -9 + 9t

Solving
0 = -9 + 9t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9t' to each side of the equation.
0 + -9t = -9 + 9t + -9t
Remove the zero:
-9t = -9 + 9t + -9t

Combine like terms: 9t + -9t = 0
-9t = -9 + 0
-9t = -9

Divide each side by '-9'.
t = 1

Simplifying
t = 1

See similar equations:

| 2(-4z-5)+16=-2(4z-3)+0 | | 17x-4(x-2)=-5 | | 5x-2+10=4x+8+10 | | 3.50=1.90+c | | -24x-31-8x+40x-9=-5x+8+15x | | Inx=-In(x+1) | | 2(3x-1)=x^2+7x-8 | | 26+4y-8=14y-10-3y | | 40*x+(12.5x*1.5)= | | 3.5h=14 | | 2.25(x-42)=x+3.28 | | 2=y/3.2 | | W/4-2=12x^4 | | 11+-12=-25 | | -4(x+3)-3=6(x-6) | | X^2-5x-5=-5 | | -2h+9h=16 | | 23+g=30 | | 10x+3=8x+18 | | 4x-6+5=2+5 | | 5v-17=78 | | 2(-2)+y=72 | | 2x=(x+4) | | (22-x)/x=-1 | | f(x)=-(x+3)*2+1 | | 3[x-4]=-4x+37 | | Y-1/6=-4/5 | | W/4-2=12x4 | | -3y+1(-9y-3)=-8+2(6-y) | | 11=3x+-25 | | 4(x+4)+2x=52 | | 30+5(x-3)=4(x+2)+3x |

Equations solver categories